Impact of residual transvalvular gradient on clinical outcomes following valve-in-valve transcatheter aortic valve replacement. (1st November 2022) - Alperi, Alberto; Robichaud, Mathieu; Panagides, Vassili; Mesnier, Jules; Nuche, Jorge; Paradis, Jean-Michel; Delarochelliere, Robert; Kalavrouziotis, Dimitri; Dumont, Eric; Mohammadi, Siamak; Rodés-Cabau, Josep
Abstract: Background: High (≥20 mmHg) postprocedural mean transvalvular gradients are relatively common among valve-in-valve (ViV) transcatheter aortic valve replacement (TAVR) recipients, but its clinical impact remains controversial. Methods: Observational study including 190 consecutive ViV-TAVR recipients. Patients were classified according to the presence of high (≥20 mmHg) or low (<20 mmHg) residual mean transvalvular gradient on post-procedural echocardiography. Functional status (NYHA class, DASI), exercise capacity (6MWT), and quality of life (KCCQ) were evaluated at baseline and at 1-year follow-up. Results: 73 (38.4%) and 117 (61.6%) patients exhibited high (HG) and low (LG) postprocedural gradients, respectively. Baseline characteristics were well balanced between groups except for a lower rate of large (>23 mm) surgical valves, atrial fibrillation, and aortic regurgitation as mechanism of valve failure in the HG group ( p  < 0.05 for all). After a median follow-up of 3 (1–5) years, there were no differences between HG and LG groups in HF hospitalization (HRadj: 1.38, 95%CI 0.44–4.22, p  = 0.57), cardiac death (HRadj: 0.50; 95%CI 0.11–2.41, p  = 0.39), all-cause mortality (HRajd: 0.71; 95%CI 0.35–1.46, p  = 0.36), or the composite endpoint of heart failure/all-cause mortality (HRadj:1.00; 95%CI 0.52–1.94, p  = 0.98). At 1-year follow-up, functional status (ΔDASI score, HG: 9.9 ± 10.9, LG: 9.9 ± 12.5, padj = 0.41), exercise capacity (Δ6MWT, HG: 111 ± 67 m, LG: 103 ± 124 m, padj = 0.14), and quality of life parameters (ΔKCCQ, HG: 27 ± 18, LG: 17 ± 21, padj = 0.12) improved similarly in both groups. Conclusions: HG as evaluated by echocardiography following ViV-TAVR were not associated with a negative effect on clinical outcomes including major adverse events, functional status, exercise capacity and quality of life parameters. Highlights: High (≥20 mmHg) residual gradients following ViV-TAVR were frequent (38.4%). High residual gradients were not associated with a negative effect on clinical outcomes and quality of life parameters.